A democracia no pensamento político dos comunistas brasileiros (1979-1983) - Ramos, Carlos Alexandre (Universidade Federal de São Carlos, 2013)
This research investigates the "democratic issue" in the political thought of the Brazilian communists. Examines how it was conceived and treated inside and around the Brazilian Communist Party (PCB) over his career, with greater interest in the period between 1979 and 1983. Seeks to demonstrate the existence of a process of emergence of "democratic issue" with its shift to the centrality of this thought. This process has been accompanied by a redefinition of the concept of democracy as the basis of their political practice. Besides extensive bibliography, sources surveyed are classified basically into three types: a) party documents, such as resolutions, reports and notes, b) publications linked to the party, such as newspapers and magazines c) theoretical production of "organic intellectuals "Party. The first chapter recalls the genesis of this thinking, identifying it in the 1940s, The second chapter discusses the formulation of the "new politics" of the PCB from 1956 with the process of "de- Stalinization" which culminates in the document known as the Declaration of March 1958. The third chapter seeks to demonstrate the "change" that suffers this thought in the "decisive moment" between 1979 and 1980, analyzing the influence of theoretical and political authors as Lukacs and Gramsci and movement Eurocommunist and also the effects of the split between Luiz Carlos Prestes and PCBs. The fourth chapter deals with the expression of this "new" thinking between 1980 and 1983, especially in the way he was treated in the newspaper Voice of Unity. The results indicate some "traces" fundamental outlined this "democratic thought." As an expression of "continuity" in relation to the genesis and development identifies the continuing design politicist understood as choice of institutional policy, the defense reiterated the broad front multiclassist and multiparty, processes Constituents and participation in elections. As expressions of "breaks" (or attempted breaches), identifies the distance of dual loyalty towards the "matrix Soviet Marxism" and how they sought to assimilate and adapt to changes in the country's political agenda, which was characterized in the last decades by a significant change in the correlation strength on the one hand, between economics and politics, and on the other, between state and society, especially the appreciation of "civil society".
Democracy in the political thought of the Brazilian communists (1979-1983)
Keywords: Partido Comunista Brasileiro; Democracia; Comunismo; Marxismo; Democracy; Marxist; CIENCIAS HUMANAS::CIENCIA POLITICA